Cost-effectiveness of the CNIC-polypill strategy for the secondary prevention of CV disease in male and female patients with established coronary heart disease based on improved risk factor control. (14th October 2021) - Aguiar, C; Araujo, F; Rubio, G; Carcedo, D; Abreu-Oliveira, T P; Paz, S; Castellano, J M; Fuster, V
Abstract: Background: The burden of CV disease is a health and economic challenge to societies that is expected to grow in future years due to an increased prevalence in CV risk factors. Adequate management and appropriate therapy positively modify risk factors and, consequently, improve outcomes and cost-effectiveness of care. The CNIC-polypill has demonstrated in real-life, clinical effectiveness studies, its superiority over monocomponents in improving the lipidic parameters and in reduction of blood pressure in secondary CV prevention patients. Purpose: To assess the cost-effectiveness of the CNIC-polypill (acetylsalicylic acid 100mg, atorvastatin 20/40mg, ramipril 2.5/5/10mg) compared to usual care with individual monocomponents for the secondary prevention of CV events in patients with a history of coronary heart disease (CHD) based on control of CV risk factors. Methods: A Markov cost-effectiveness model (1-year cycles; 4 health states: stable disease, subsequent CHD, subsequent stroke, death; payer perspective; direct medical costs; lifetime horizon; 4% discount rate) based on changes in TC (10, 1% reduction), HDL-c (7.4% increment) and SBP (2.6% reduction) obtained from the NEPTUNO* – a real-life, clinical effectiveness study conducted in Spain – was set for Portugal (base case). The probability of transition between health states was based on the SMART risk equation (S0, t=10= 0.8107). Cost-effectiveness was calculated for a hypothetical population (n=1, 000) that replicated the characteristics of the population in the proACS registry, comprised of Portuguese patients with previous CHD. Systematic reviews identified epidemiological, costs, utility and mortality data. Outcomes were costs (€, 2020), life years (LY) and quality adjusted LY (QALY) gained. Results: In patients with a history of CHD, the incremental cost of the CNIC-polypill strategy reaches €365, 527, while preventing 35 recurrent CHD events and 17 subsequent strokes. In women and men with previous CHD, the incremental cost reaches €392, 529 and €354, 444 respectively while preventing recurrent 47 and 30 CHD events and 19 and 16 subsequent strokes respectively. The ICER is €5, 130/LY gained for the overall population, €5, 768/LY gained for women and €4, 884/LY gained for men. The ICUR is €5, 332/QALY gained in total, €5, 817/QALY gained for women and €5, 137/QALY gained for men. Assuming a willingness-to-pay (WTP) threshold of €30, 000/QALY gained, there is 76.1% chances in total, 75.8% in women and 76.9% in men for the CNIC-polypill to be cost-effective and 27.8% chances overall, 27.7% in women and 25.5% in men of it being cost saving compared to usual care. Conclusion: The CNIC-polypill seems to be a cost-effective strategy in men and women compared to usual care with monocomponents for the secondary prevention of CV disease based on improved control of risk factors. A larger reduction in the number of recurrent events is seen in women compared to men at a slightly higher cost. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Ferrer International S.A.